IgG Subclass Determines Suppression Versus Enhancement of Humoral Alloimmunity to Kell RBC Antigens in Mice - Shinde, Paurvi; Howie, Heather L.; Stegmann, Tamara C.; Hay, Ariel M.; Waterman, Hayley R.; Szittner, Zoltan; Bentlage, Arthur E. H.; Kapp, Linda; Lissenberg-Thunnissen, Suzanne N.; Dekkers, Gillian; Schasfoort, Richard B. M.; Ratcliffe, Sarah J.; et al. (Frontiers in Immunology, 2020)
It has long been appreciated that immunoglobulins are not just the effector endpoint of humoral immunity, but rather have a complex role in regulating antibody responses themselves. Donor derived anti-RhD IgG has been used for over 50 years as an immunoprophylactic to prevent maternal alloimmunization to RhD. Although anti-RhD has dramatically decreased rates of hemolytic disease of the fetus and newborn (for the RhD alloantigen), anti-RhD also fails in some cases, and can even paradoxically enhance immune responses in some circumstances. Attempts to generate a monoclonal anti-RhD have largely failed, with some monoclonals suppressing less than donor derived anti-RhD and others enhancing immunity. These difficulties likely result, in part, because the mechanism of anti-RhD remains unclear. However, substantial evidence exists to reject the common explanations of simple clearance of RhD+ RBCs or masking of antigen. Donor derived anti-RhD is a mixture of 4 different IgG subtypes. To the best of our knowledge an analysis of the role different IgG subtypes play in immunoregulation has not been carried out; and, only IgG1 and IgG3 have been tested as monoclonals. Multiple attempts to elicit alloimmune responses to human RhD epitopes in mice have failed. To circumvent this limitation, we utilize a tractable animal model of RBC alloimmunization using the human Kell glycoprotein as an antigen to test the effect of IgG subtype on immunoregulation by antibodies to RBC alloantigens. We report that the ability of an anti-RBC IgG to enhance, suppress (at the level of IgM responses), or have no effect is a function of the IgG subclass in this model system.